(untitled) (Вестник транспорта - Transport xabarnomasi, 2025)
management, revolutionizing customer service and operational efficiency. This paper explores the impact of AI-driven tools, such as Speech-to-Text (STT) and Text-to-Speech (TTS) systems, on call centre performance and economic outcomes, focusing on the rapidly growing market in Uzbekistan. Drawing on qualitative interviews and quantitative market data, this research highlights how AI improves operational efficiency through customer conversation analysis, error tracking, and sentiment analysis. Additionally, the study provides a statistical forecast on market capture, showing potential growth trends for AI-based startups in Uzbekistan’s telecommunications, EdTech, retail, and other key sectors. With a Serviceable Obtainable Market (SOM) of 1% and a n optimistic growth outlook, this paper argues that AI tools offer considerable strategic value for businesses aiming to enhance customer satisfaction and optimize service operations.